Comparative constitutionalism and good governance in the Commonwealth: An Eastern and Southern African perspective - Hatchard, John (Cambridge University, 2013)
Key constitutional issues in the process of developing, strengthening and consolidating the capacity of states to ensure good governance are analysed here. Utilising comparative material, the book draws lessons about the problems of constitutionalism and critically addresses the legal issues involved in making constitutions 'work' in practice.